Penerapan E-Government dalam Pelayanan Publik melalui Sistem Penandatanganan Elektronik (Sakato Sign) Studi pada DPMPTSP Provinsi Sumatera Barat - Zandri, Ilham; Syamsir, Syamsir (PUBLICNESS: Journal of Public Administration Studies, 2023)
The research conducted is descriptive research with a qualitative approach, which provides a real picture of the application of Sakato Sign and continuous data analysis process to understand the natural condition of objects. However, the implementation of the Sakato Sign faces several obstacles. First, system limitations that can only be used on Android-based devices, not on various device platforms. Second, dependence on a stable internet connection due to online technology-based systems. Third, errors often occur on the system due to server sharing with other systems. And fourth, the completion time for signing is still not fully in accordance with the Standard Operating Procedures. To overcome these obstacles, the Service needs to communicate with related parties, evaluate, repair, and upgrade the Sakato Sign system. Improvement of device compatibility and internet connection management should be pursued. Agencies also need to comply with SOPs and engage in staff training to increase the effectiveness of e-government implementation in public services through the Sakato Sign electronic signing system. Thus, it is hoped that the implementation of e-government can run more efficiently and effectively, provide more accessible public services and increase community satisfaction.